Environment Act 2021 : Text, Guide and Analysis - Badger, Christopher; Macrory, Richard, Hon QC (London : Hart Publishing, 2022)
The Environment Act 2021 is the most wide-reaching and significant new environmental Statute for many years. In this book, the full text of the Act is reproduced, accompanied by commentary and a section-by-section analysis written by 2 of the UK's leading experts in environmental law. The book comments on and analyses the main provisions of the Act, including: - A requirement on government to establish long-term environmental targets and environmental improvement plans; - Legal recognition for the first time in national law of a number of core environmental principles, including the precautionary principle and the polluter pays principle; - The establishment of a new independent statutory body, the Office for Environmental Protection; - Substantial provisions on waste including producer responsibility and resource efficiency; - Provisions on water resource management, water abstraction and drainage and sewerage; - Strengthening of controls on air quality; and - New provisions concerning the protection of nature and biodiversity, including the creation of conservation covenants. This comprehensive and practical guide to the new legislation will be of significant value to anyone involved in environmental law in both the private and public sector, in particular practitioners and those advising on the impact and ambit of environmental law.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Environmental law -- Great Britain; Law commentaries; Environment law; United Kingdom